1991
DOI: 10.1007/bf02555898
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral bone in osteoarthritis

Abstract: To determine whether subchondral bone in osteoarthritis differs from that seen in normal human aging, osteoarthritic femoral heads removed for total hip arthroplasty were compared with normal age-matched and young autopsy controls. Standardized, 1-cm deep, weight-bearing and nonweight-bearing subchondral bone blocks, as well as cancellous core bone, 2-4 cm deep on the articular surface, were examined in each femoral head. Mineralization was assessed using density fractionation and chemical analysis, and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
153
2
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(174 citation statements)
references
References 18 publications
16
153
2
3
Order By: Relevance
“…(52) While there are some early signs of progress in understanding the molecular control of osteocyte differentiation from the osteoblast, with oncostatin M promoting differentiation along this pathway in tumor cells, (53) the regulation of osteocyte formation remains largely obscure in molecular terms. Whether mineralization is reduced in OA is a matter of debate because studies have reported that in hip OA, femoral head cancellous (5) and subchondral bone (54) is less mineralized, contrasting with iliac cortical bone, which is more highly mineralized in OA. (55) Boneformation rates are higher in subchondral bone in OA.…”
Section: Discussionmentioning
confidence: 99%
“…(52) While there are some early signs of progress in understanding the molecular control of osteocyte differentiation from the osteoblast, with oncostatin M promoting differentiation along this pathway in tumor cells, (53) the regulation of osteocyte formation remains largely obscure in molecular terms. Whether mineralization is reduced in OA is a matter of debate because studies have reported that in hip OA, femoral head cancellous (5) and subchondral bone (54) is less mineralized, contrasting with iliac cortical bone, which is more highly mineralized in OA. (55) Boneformation rates are higher in subchondral bone in OA.…”
Section: Discussionmentioning
confidence: 99%
“…The bone closest to the articular cartilage has the greatest effect on cartilage integrity, with variations in stiffness and BMD probably causing more damage to cartilage than any other parameters under normal conditions [27,28]. Although OA at a later stage demonstrates a thickening of subchondral bone, explants of the femoral heads of OA patients at autopsy revealed a pattern of low mineralisation compared with that of normal [29,30]. Hence, the apparent increase in bone density in OA may be because of an increase in material density, and not mineral density [31][32][33].…”
Section: Correlation Between In Vivo Findings In Animals and Human Oamentioning
confidence: 99%
“…As mentioned above, some studies have indicated that subchondral bone changes precede and may be responsible for the evolution of cartilage lesions [29,95,96]. Others have indicated that subchondral bone changes would only be secondary to cartilage degradation [97,98].…”
Section: Interaction Between Subchondral Bone and Cartilagementioning
confidence: 99%
“…Initial work by Radin and colleagues suggested that, as a consequence of thickening and repair of trabecular microfractures, the subchondral plate was stiffened and stress increases within the overlying cartilage combined with repeated impact loading led to deterioration of the cartilage (Radin et al, , 1973. Additional studies in humans and animal models have confirmed that there are density-related changes in the subchondral bone in individuals with osteoarthritis (Radin et al, 1970b;Radin and Rose, 1986;Brandt et al, 1991;Grynpas et al, 1991;Dedrick et al, 1993;Matsui et al, 1997;Hayami et al, 2004;Wang et al, 2005), but whether the subchondral changes precede or follow the osteoarthritis remains a matter of continuing debate (Burr and Radin, 2003;Wang et al, 2005).…”
mentioning
confidence: 99%